Ultrasonically Dispersed Ionic Liquid-Based Microextraction of Lead in Biological Samples of Malnourished Children Prior to Analysis by Flame Atomic Absorption Spectrometry. (23rd November 2019) - Talpur, Sehrish; Kazi, Tasneem Gul; Afridi, Hassan Imran; Talpur, Farah Naz; Nizamani, Sooraj; Lashari, Anjum; Akhtar, Asma; Khan, Mustafa
Abstract: In the present study, a simple ultrasonically dispersed modified liquid-phase microextraction method was developed for the extraction of lead (Pb) from blood and scalp hair samples of malnourished children (MNC). The complexation of Pb was executed by means of the complexing agent, ammonium pyrrolidinedithiocarbamate (APDC), whereas extraction was carried out through the ionic liquid (IL), 1-butyl-3-methylimidazolium hexafluorophosphate. Ultrasound energy was used for the dispersion and extraction of the metal complex into an IL because it enhances the extraction of the metal complex into infinite IL drops at a temperature range of 40–80°C for 1–5 min. After sonication, the enriched analyte phase was separated by centrifugation. Nitric acid (HNO3 ; 0.5–2 mol/L) was added to the IL-enriched phase to back-extract the analyte into the acidic aqueous phase and analyzed by flame atomic absorption spectrometry. Various experimental parameters that affect the efficiency of the proposed method, such as volume of IL, concentration of the complexing agent, pH, ultrasonication time and temperature, and concentration of HNO3, were optimized. The enhancement factor was calculated as 70. The LOD for Pb ions was found to be 0.19 μg/L, with an RSD of <5%. Accuracy was ensured by applying the procedure to a certified reference material for whole blood and scalp hair. The developed procedure was successfully applied for the analysis of the concentration of Pb ion in whole-blood and scalp hair samples of MNC from different areas of Sindh, Pakistan. The concentration of Pb among MNC was 2-fold higher than the referent.